Progress in the Study of Precambrian Systems Using Cyclic Stratigraphy - Li, Ting (International Journal of Natural Resources and Environmental Studies, 2025)
The history of Earth's evolution shows that environmental changes have led to multiple major biological evolution events and altered the course of life evolution on Earth. Clarifying the timing and underlying mechanisms of these environmental upheavals is of great significance for us to respond to today's global changes. The Pre Cambrian period occupies the vast majority of geological history, exhibiting changes and evolution in atmospheric composition, paleoclimate, life, and other aspects at different time scales. In recent years, a large number of reliable Milankovitch cycle records have been identified in pre-Cambrian strata worldwide. With the help of various sedimentary cycle analyses, it is expected to establish a high-resolution chronological framework for the early evolution of the Earth, obtain data on planetary orbital interactions, and reconstruct the history of celestial dynamics. Through the main examples of pre-Cambrian cycle stratigraphy research, this paper analyzes the key issues and main challenges of pre-Cambrian cycle stratigraphy research, such as alternative indicators of primitive climate, reconstruction of celestial dynamics models, complex climate models, and paleogeographic uncertainties. It attempts to propose solutions to these problems.